Pemekaran Kota Sofifi Maluku Utara sebagai Daerah Persiapan Otonomi Baru Ditinjau dari UU No 23 Tahun 2014 - Awaluddin Awaluddin; Idzam Faitanu; Hasbi Hasan (Jurnal Penelitian Hukum Legalitas, 2016)
This study aims to examine and analyze the process and constraints expansion city of Sofifi North Maluku as a new autonomy preparation area in the review of Law no. 23 years 2014. This study is an analytical descriptive that describes the detailed description of the processes and barriers to the expansion of Sofifi as a new Autonomy Preparation area. The approach used is an empirical juridical approach that emphasizes literature research/law and field research results. Based on the results of this study submitted suggestions To the Governor of North Maluku Province and the Mayor of Tidore island immediately coordinate discuss the barrier of expansion city of Sofifi North Maluku. Mayor of Tidore Town and Tidore Islands Municipal People's Legislative Assembly immediately issue the recommendation of approval of the release of sofifi area to fulfill the administrative requirement in regional expansion. DPR-DPD RI immediately ratified the regulation on the DESARTADA as the implementing rule and the guidance of regional expansion, and revised Article 33 paragraph 3 of the preparatory areas that priority areas such as Sofifi of North Maluku no need to use the concept of preparation area or the gap period because sofifi has not fulfilled the Government Convention Regions, that is each provincial capital must be a city.